A review of the geologic sections and the faunal assemblages of Aurelian Mammal Age of Latium (Italy) in the light of a new chronostratigraphic framework. (1st February 2018) - Marra, F.; Nomade, S.; Pereira, A.; Petronio, C.; Salari, L.; Sottili, G.; Bahain, J.-J.; Boschian, G.; Di Stefano, G.; Falguères, C.; Florindo, F.; Gaeta, M.; et al.
Abstract: The Aurelian Mammal Age for peninsular Italy was introduced on the basis of faunal assemblages mainly recovered at sites along the Via Aurelia west of Rome. These sites exposed a set of sedimentary deposits currently attributed to the Aurelia and to the Vitinia Formations correlated with MIS 9 and MIS 7, respectively. In the present paper we reconstruct the geologic-stratigraphic setting in the western sector of Rome within the wider context of glacio-eustatically controlled, geochronologically constrained aggradational successions defined for this region. We present a chronostratigraphic study based on dedicated field surveys, that, combined with five new 40 Ar/ 39 Ar ages and eighteen trace-element and EMP glass analyses of volcanic products, allow us to revise age and correlation with the Marine Isotopic Stages for 10 sites out of 12 previously attributed to the Aurelia Formation and the Torre in Pietra Faunal Unit. In particular, we demonstrate a MIS 13/MIS 11 age for several sections along the Via Aurelia between Malagrotta and Castel di Guido. Based on this new geochronological framework, the first occurrences of Canis lupus and Vulpes vulpes in Italy are antedated to MIS 11, within the Fontana Ranuccio Faunal Unit of the Galerian Mammal Age, consistent with the wider European context. This contribution is intended as the groundwork for a revision of the Middle Pleistocene Mammal Ages of the Italian peninsula, according to the improved chronostratigraphy of the geologic sections hosting the faunal assemblages. Highlights: We provide precise chronostratigraphic framing to several archaeologic sites in the area of Rome. We provide new geochronologic constraints to the faunal assemblages of the Aurelian Mammal Age. We revise the chronology of Castel di Guido, Malagrotta and Riano archaeological sites. We revise the depositional context of La Polledrara di Cecanibbio archaeological site. We revise the first occurrences of Canis lupus and Vulpes vulpes in Italy.